Sistem Penggalangan Dana Zis Menggunakan Metode Crowdfunding Pada Masjid Ar-Ruhaniyah Kabupaten Tangerang, Banten - Mahbubi .; Muhammad Nur Fadillah; Sungkono .; syamsunasir . (Fakultas Ilmu Komputer dan Desain - Unsurya, 2023)
This research was conducted to create an online fundraising system that can facilitate the donation process, collect donor data, and financial reports at the Ar-Ruhaniyah Mosque Amil Zakat and Sedekah Institution (LAZIS). Previously, the management of donations at the institution still used a manual process that was inefficient, causing problems in collecting donation data and disbursing funds, and reducing people's interest in giving alms. This study uses qualitative methods and the Waterfall design method, as well as the Crowdfunding method approach. The system created is website-based with design and modeling using Data Flow Diagrams (DFD) diagrams and tested using the Blackbox and Whitebox testing methods. The result of this research is an online fundraising system that can facilitate the donation process, collect donor data, and financial reports at the institution.Â Keywords: Fundraising, Crowdfunding, Website, Mosque, Lazis.